Gaslighted : how the oil and gas industry shortchanges women scientists - Williams, Christine L., 1959- (Oakland, California : University of California Press, 2021)
"The oil and gas industry is one of the richest and most powerful industries in the world. In recent years, company avowals in support of diversity, much-touted programs for 'women in STEM,' and, most importantly, a tight labor market with near parity in women pursuing geoscience credentials might lead us to expect progress for women in this industry's corporate ranks. Yet, for all the talk of 'the great crew change,' the industry remains overwhelmingly white and male. Sociologist Christine L. Williams asks, where are the women? To answer this question, Williams embarked on a decade-long investigation--one involving one hundred in-depth interviews, a longitudinal survey, and ethnographic research--that allowed her to observe the industry in times of boom and bust. She found that when the industry expands, women may be able to walk through the door, but when the industry contracts, the door becomes a revolving one, whirling ever faster, as companies retreat to their white male core. These gendered outcomes are obscured by firms' stated commitment to diversity in hiring and the language of merit. The result is organizational gaslighting, a radical dissonance between language and practice that Williams exposes for all"--
Introduction -- The oil and gas pipeline -- The stayers -- Voluntary separations -- Corporate downsizing -- Conclusion -- Methodological appendix.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on October 06, 2021).
JSTOR
Keywords: Oil industries -- United States -- Employees; Gasoline industry -- United States -- Employees; Women earth scientists -- United States; Sex discrimination against women -- United States; Essence -- Industrie -- États-Unis -- Personnel; Femmes spécialistes des sciences de la terre -- États-Unis.; Discrimination à l'égard des femmes -- États-Unis.; SOCIAL SCIENCE / Gender Studies; Oil industries -- Employees; Sex discrimination against women; Women earth scientists; United States